The top 10 things you must know about measuring ROI on social media marketing - Turner, Jamie, 1961- (FTPress Delivers, 2011)
Skills, facts, strategies, techniques...whatever it takes! FT Press's quick new Top 10s bring together the 10 most crucial things you MUST know to get great results, right now! Ten powerful techniques and crucial insights for measuring social media ROI--and optimizing it! When you think about it, the only truly important social media metric is good old return on investment (ROI). Everything else--traffic, comments, followers, leads--is just a stop along the way. Without positive ROI, there's really no reason to run a social media campaign. Here are ten things you must know to measure the effectiveness of social marketing....